Surgical Approach to Control Advanced Coats Disease: Doi:10.36351/pjo.v36i4.1112 - Özdek, Şengül; Üçgül, Ahmet Yücel (Pakistan Journal of Ophthalmology, 2020)
Coats disease, first described by George Coats in 1908, is commonly a unilateral clinical entity characterized by leaky telangiectatic vessels leading to progressive subretinal exudation and exudative retinal detachment (ERD).1 It is generally seen in pediatric population and has a distinct male predilection of over 90%. Shields et al.2 classified Coats disease into five stages as follows: Stage 1: presence of retinal telangiectasia only, Stage 2: telangiectasia and exudation (2A: extrafoveal exudation, 2B: foveal exudation), Stage 3: exudative RD (3A: subtotal RD, 3B: total RD), Stage 4: total RD and neovascular glaucoma, Stage 5: advanced end-stage disease. Disease progression can be controlled with ablative therapies such as laser photocoagulation (LFK) and cryotherapy in the early stages of Coats disease. However, ablative therapies are not effective in the late stages (Stage 3 – 4) due to excessive subretinal exudation and ERD. Therefore, adjunctive surgical approaches have become popular in the treatment of advanced Coats disease. This helps in effective ablation of leaky abnormal vessels.